Nutrient Limitation Governs Staphylococcus aureus Metabolism and Niche Adaptation in the Human Nose - Krismer, Bernhard (Public Library of Science, 2014)
Colonization of the human nose by Staphylococcus aureus in one-third of the population represents a major risk factor for invasive infections. The basis for adaptation of S. aureus to this specific habitat and reasons for the human predisposition to become colonized have remained largely unknown. Human nasal secretions were analyzed by metabolomics and found to contain potential nutrients in rather low amounts. No significant differences were found between S. aureus carriers and non-carriers, indicating that carriage is not associated with individual differences in nutrient supply. A synthetic nasal medium (SNM3) was composed based on the metabolomics data that permits consistent growth of S. aureus isolates. Key genes were expressed in SNM3 in a similar way as in the human nose, indicating that SNM3 represents a suitable surrogate environment for in vitro simulation studies. While the majority of S. aureus strains grew well in SNM3, most of the tested coagulase-negative staphylococci (CoNS) had major problems to multiply in SNM3 supporting the notion that CoNS are less well adapted to the nose and colonize preferentially the human skin. Global gene expression analysis revealed that, during growth in SNM3, S. aureus depends heavily on de novo synthesis of methionine. Accordingly, the methionine-biosynthesis enzyme cysteine-γ-synthase (MetI) was indispensable for growth in SNM3, and the MetI inhibitor DL-propargylglycine inhibited S. aureus growth in SNM3 but not in the presence of methionine. Of note, metI was strongly up-regulated by S. aureus in human noses, and metI mutants were strongly abrogated in their capacity to colonize the noses of cotton rats. These findings indicate that the methionine biosynthetic pathway may include promising antimicrobial targets that have previously remained unrecognized. Hence, exploring the environmental conditions facultative pathogens are exposed to during colonization can be useful for understanding niche adaptation and identifying targets for new antimicrobial strategies.